INTRODUCTION. (24th October 2014) - Mandler, Peter
Abstract : This volume of Transactions is notable not only – of course – for what it contains, but also for what it does not contain. Readers will find the usual varied fare of papers read at the Society's meetings – the cream of recent scholarship – as well as three of the papers read at the colloquium on 'Croatia and Europe' held at the University of Leicester on 27 March 2013 to mark Croatia's entry into the European Union – an unusual and timely reminder of an important geopolitical story not often included in standard accounts of European history. As for the missing contents – with this volume, Transactions will no longer include the Society's annual report and accounts. This change will decouple the publication of report and accounts necessary for the AGM from the publication of Transactions and will enable us to include more academic content in the latter. The annual report and accounts will be made more widely available by publication before the AGM in November on the Society's new website (www.royalhistsoc.org ). I encourage all Fellows and Members to take a look, not only for the full annual report, but also for the wide range of new resources now available on the website: an archive of policy documents (the Society's but also other scholarly and public bodies), on subjects ranging from the school curriculum to freedom of information; podcasts of all of the Society's recent public lectures; information on upcoming events of interest to historians; application forms for proposing new Fellows and Members and applying for the Society's early career research grants and fellowships; a guide for early career historians; and much more relevant not only to the Society's activities but to the rich world of historical research beyond.